2004
DOI: 10.1101/gr.2300204
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Topology in the Yeast Protein Interaction Network

Abstract: The integrity of the yeast protein-protein interaction network is maintained by a few highly connected proteins, or hubs, which hold the numerous less-connected proteins together. The structural importance and the increased essentiality of these proteins suggest that they are likely to be conserved in evolution, implying a strong relationship between the number of interactions and their evolutionary distance to its orthologs in other organisms. The existence of this coherence was recently reported to strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 27 publications
10
80
1
Order By: Relevance
“…For convenience, we will consider the corresponding interaction networks linking genes whose protein products interact physically and we will refer to the topological parameters of these gene interaction networks. Several authors have found that the fraction of essential genes is 3 to 5 times higher among highly connected genes than among low-connected genes and have proposed that the phenotypic consequences of a gene deletion in yeast are affected to a large extent by the gene degree in the interaction networks ( Jeong et al 2001;Wuchty 2004;Yu et al 2004). However these analyses used data derived from Uetz et al (2000) and/or from the DIP database (Xenarios et al 2000), which present some biases.…”
Section: Results (A)mentioning
confidence: 99%
“…For convenience, we will consider the corresponding interaction networks linking genes whose protein products interact physically and we will refer to the topological parameters of these gene interaction networks. Several authors have found that the fraction of essential genes is 3 to 5 times higher among highly connected genes than among low-connected genes and have proposed that the phenotypic consequences of a gene deletion in yeast are affected to a large extent by the gene degree in the interaction networks ( Jeong et al 2001;Wuchty 2004;Yu et al 2004). However these analyses used data derived from Uetz et al (2000) and/or from the DIP database (Xenarios et al 2000), which present some biases.…”
Section: Results (A)mentioning
confidence: 99%
“…The indispensability of a gene defines its functional significance and when such genes are knocked out the cell becomes unviable [15]. The yeast PIN has also been the objective of several other topological analyses aimed at the detection of protein functionality and evolution [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…16 Previously, there was not a consensus whether hubs were slower-evolving than other proteins or not. 2,5,12,30 Kim et al 16 by integrating structures into protein interaction networks stated that multi-interface hubs were more likely to be essential and more conserved, being members of large and stable complexes as opposed to singlish-interface hubs. In a proceeding study, they found that although singlishinterface hub proteins were more disordered, their interfaces were highly structured, as is the case for multi-interface hubs.…”
Section: Introductionmentioning
confidence: 99%